Sistem Deteksi Posisi Dan Pengambilan Bola Pada Robot Sepak Bola - Amperawan, Amperawan; Andika, Destra; Anisah, Masayu; I.J, Marcelinus (Jurnal Ampere, 2022)
One of the robot contests held in Indonesia at regional and national levels is the Indonesia Sepal Bola Robot Contest (KRSBI) with wheels, which is a part of the Indonesian Robot ContestÂ  which is a design and engineering competition in the field of robotics. KRSBI in 2017 is a new division organized by RISTEKDIKTI with the theme "Robot football to the soccer league in 2050." The attacking robot determines the position and control ball taker using Arduino Mega board and open CV software on a laptop pad. Some of the sensors used in robotic sensors are compass sensors, camera sensors, encoders and infrared sensors. The infrared sensor functions to detect the presence of a ball in the robot'sÂ  arm. In detecting the ball using a camera sensor where the farthest distance to detect the ball is 6 meters, the compass sensor knows the angle of the robot's position and the position of the goalpost. With the research "Position Detection And Ball Taker SystemÂ Â  OnÂ  Robot Soccer" can answer this problem by assisting the robot in detecting and retrieving the ball and directing the robot towards the goal. This research goes through stages including system design from hardware and software as well as system testing and data collection.Â ABSTRAKSalah satu kontes robot yang di adakan di IndonesiaÂ  tingkat regionalÂ  dan nasionalÂ  adalah Kotes RobotÂ  Sepal Bola Indonesia (KRSBI)Â  beroda adalah salah satu bagian dari Kontes Robot Indonesia yang merupakan ajang kompetisi rancang bangun dan rekayasa di bidang robot.Â  KRSBI pada tahun 2017 merupakan divisi baru diselengarakanÂ  Pada robotÂ  penyerangÂ  penentu posisi dan pengambil bolaÂ  pengendalinyaÂ  menggunakan board Arduino Mega dan software OpenCVÂ  padÂ  laptop. BeberapaÂ  yang digunakan pada robot sensor yaitu sensor kompas, sensor kamera,Â Â  encoder dan sensor infra red.Â  Sensor infra red fungsinya untuk mendeteksi adanya bola dilengan robot,Â  dalam pendeteksian bola menggunakan sensor kamera yang dimana jarak terjauhÂ  mendeteksi bola 6 meter, sensor kompasÂ  mengetahui sudutÂ Â  posisi robot danÂ  posisi tiang gawang. Dengan penelitian â€œSistemÂ  DeteksiÂ Â  PosisiÂ Â  DanÂ  Pengambil Bola Pada RobotÂ  SepakÂ  Bolaâ€Â  dapat menjawab masalah tersebut dengan membantu robot dalam medeteksi dan pengambilan bolaÂ  serta mengarahkan robot ke arah gawang.Â  Penelitian iniÂ  melaluiÂ  tahapan diantaranyaÂ  adalahÂ  perancangan sistem dari hardware dan software serta dilakukanÂ  pengujian sistem dam pengambilan data.